Holocaust Film before the Holocaust: DEFA, Antifascism and the Camps - Bathrick, David (Cinémas, 2007)
AbstractThe period prior to the 1970s has frequently been portrayed internationally as one of public disavowal of the Jewish catastrophe politically and cinematically and as one in which there was a dearth of filmic representations of the Holocaust. In addition to the Hollywood productions The Diary of Anne Frank (1960), Stanley Kramer’s Judgment at Nuremberg (1961) and Sidney Lumet’s The Pawnbroker (1965), one often spoke of just a few East and West European films emerging within a political and cultural landscape that was viewed by many as unable or unwilling to address the subject. This article takes issue with these assumptions by focusing on feature films made by DEFA between 1946 and 1963 in East Berlin’s Soviet Zone and in East Germany which had as their subject matter the persecution of Jews during the Third Reich.